Menakar Kelayakan Bisnis Kripik Lidah Buaya - Risxa Ayu Anggreani; Laily Nurjanah; Tia Masherly Berlianna; Siti Mudzalifah; Tatanka Rizky Adinugroho; Hendra Dwi Prasetyo (Universitas Pendidikan Nasional, 2021)
This research aims to find out whether or not the business of the Aloe Vera Kripik Business is produced by Alove.it team. The non-financial feasibility aspects used in the analysis of this research are aspects of production and marketing. As for the financial aspects used, namely payback period analysis tools, Net present value, Internal Rate of Return, and Profitability Index, to determine whether an effort is worth doing. The results obtained in this study that the Aloe Vera Kripik Business Alove.it from the results of the production aspects of this Alove.it business is declared feasible because the location is on the roadside, strategically profitable, and easily accessible to consumers, the technology used is cutting-edge and the manufacturing process is simple. From the marketing, aspect is stated quite well and decent, with high-quality products, affordable prices, and make good use of the role of social media where everyone can more easily buy it, the breadth of distribution reach, and advertise offered by the owner is enough to make consumers familiar with this product. In terms of finances shown that this Aloe Vera Kripik Business is said to be worth developing because the value results are above the minimum standard of investment. By generating Payback period for 21 days, net present value of Rp 2,284,416.5, Profitability Index value of 26.8%, and, Internal Rate of Return of 56%.